1990
DOI: 10.1152/ajpgi.1990.259.3.g372
|View full text |Cite
|
Sign up to set email alerts
|

Uphill transport of beta-alanine in intestinal brush-border membrane vesicles

Abstract: The characteristics of beta-alaline uptake were studied in brush-border membrane vesicles isolated from the proximal small intestine of rabbits and were compared with those of L-alpha-alanine uptake. The uptake of beta-alanine as well as L-alpha-alanine was significantly stimulated by imposing an inwardly directed Na+ gradient. Studies on transstimulation and substrate specificity provide evidence that the transport system serving beta-alanine is distinct from the system serving alpha-alanine. The beta-system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 0 publications
1
15
0
2
Order By: Relevance
“…The kinetical data of the p-alanine transport by muscle cells also compare well with the data reported for other systems such as the high-affinity low-capacity p-alanine uptake system of renal [4] and intestinal [7] brush border membranes.…”
Section: Discussionsupporting
confidence: 82%
“…The kinetical data of the p-alanine transport by muscle cells also compare well with the data reported for other systems such as the high-affinity low-capacity p-alanine uptake system of renal [4] and intestinal [7] brush border membranes.…”
Section: Discussionsupporting
confidence: 82%
“…H'-coupled /I-alanine transport was inhibited by L-alanine [14] and L-proline (unpublished observation). In contrast, studies in rabbit intestinal BBMV demonstrated that NaCl-dependent j?-alanine transport was unaffected by L-alanine or Lproline [20] and p-alanine is not an inhibitor of Na'-dependent proline transport by the Imino carrier [5]. Although proline was a potent inhibitor of H'-coupled B-alanine transport and accumulation the question of whether these two substrates are transported by a single H'-coupled carrier is a difficult one to approach and remains to be answered.…”
Section: Discussionmentioning
confidence: 84%
“…Transport is dependent upon Na + and Cl ¡ in the ratio 2:1:1 (Na + :Cl ¡ : -alanine) (Miyamoto et al 1990;Ramamoorthy et al 1994;Bakardjiev and Bauer 1994;Komura et al 1996). -alanine transport exhibits Michaelis-Menten kinetics with a Km in chick pectoral muscle of approximately 40 M (Bakardjiev and Bauer 1994;Kalyankar and Meister 1959;Winnick and Winnick 1959).…”
Section: Discussionmentioning
confidence: 99%